EVALUATION OF PEROXYDASE ACTIVITY IN SAMPLES FROM THREE POTATO VARIETIES INOCULATED WITH POTATO VIRUS S AND M CULTIVATED UNDER DROUGHT CONDITIONS - CIOLOCA, Mihaela; BADARAU, Carmen Liliana; TICAN, Andreea; MOJA, Adelina; MUNTEANU-ICHIM, Roxana Andreea (Agricultural Research and Development Station Lovrin, 2025)
Drought stress and virus infections are some of the major problems for potato production. Peroxidase (POD) activity could be an important indicator of potato growing process, reflecting the antioxidant capacity of plants, peroxidase being an enzyme with a strong contribution to the defense system of vegetables. This study presents the POD activity estimated in healthy plants and potato viruses S (PVS) and M (PVM) infected plants (from the Romanian varieties Cosiana, Azaria and Sevastia) cultivated in greenhouse, under salt and drought conditions (salt stress induced by plants irrigation with a solution NaCl 2g/L). The results show that the POD activity was influenced significantly by the PVS and PVM plants inoculation (especially in case of samples from resistant varieties to these viruses) and the antioxidant response of the potato plants was more intensive under drought conditions and under biotic stress (viruses inoculated).
Keywords: salt stress; POD activity; potato cultivars; PVM; PVS